Three new long-chain polyenes from the mangrove-derived fungus Penicillium herquei JX4. Issue 5 (4th May 2023) - Long, Kai-Yuan; Dai, De-Cai; Zheng, Cai-Juan; Wang, Yi-Tong; Song, Xin-Ming; Chen, Xuan; Zhou, Xue-Ming; Chen, Guang-Ying
Abstract: One new epimer pair of long-chain polyenes penicilqueis E (1 ) and F (2 ), and one new long-chain polyene pinophol G (3 ), along with one known compound (4 ), were obtained from EtOAc extract of the mangrove-derived fungus Penicillium herquei JX4. Their structures were elucidated by detailed analysis of comprehensive spectroscopic data. The inhibitory activities of all compounds against the nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells in vitro were evaluated. Graphical Abstract: UF0001